2018
DOI: 10.1002/jso.25106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fluorescence‐guided surgery of peritoneal carcinomatosis of colorectal origin: A narrative review

Abstract: Patients with peritoneal carcinomatosis (PC) from colorectal origin may undergo cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) as a curative approach. One major prognostic factor that affects survival is completeness of cytoreduction. Molecular Fluorescence Guided Surgery (MFGS) is a novel intraoperative imaging technique that may improve tumor identification in the future, potentially preventing over‐ and under‐treatment in these patients. This narrative review outlines a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 126 publications
0
13
0
Order By: Relevance
“…From a dosing point of view, virtually all series carry the same dosage (0.25 mg/kg), except one that carries twice and one that uses a fixed dose independently from weight (20 mg). All reported injected schedules are similar to that used in other areas for perfusion studies [19].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…From a dosing point of view, virtually all series carry the same dosage (0.25 mg/kg), except one that carries twice and one that uses a fixed dose independently from weight (20 mg). All reported injected schedules are similar to that used in other areas for perfusion studies [19].…”
Section: Discussionmentioning
confidence: 81%
“…It is a low-cost molecule, easy to use, widely available and with negligible toxicity [17]. The use of ICG fluorescence in abdominal surgery has been introduced in recent years and represents a common tool for perfusion evaluation, extrahepatic bile duct anatomy, lymph node navigation and liver surgery [18][19][20]. ICG binds primarily to serum albumin and other serum globulins such as alpha1-lipoprotein, and then it circulates behaving like a macromolecule [21].…”
Section: Discussionmentioning
confidence: 99%
“…After some initial cases, almost all the Authors injected ICG at the time of anesthesia induction and detected fluorescence starting from 5′ after the injection, for a rather long period (someone up to 360′). Some experimental observations suggested that the best timing for ICG visualization due to the EPR is 6 h after injection owing to the rapid clearance of ICG, resulting in a better tumor-to-background ratio starting after 6 h and lasting until 24 h [27]. In case of HCC the timing is different, as ICG is metabolized by normal hepatocytes and unexcreted because of bile ducts alteration, elightening the nodules even many days after the injection.…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental observations suggested that the best timing for ICG visualization due to the EPR is 6 hours after injection owing to the rapid clearance of ICG, resulting in a better tumor-to-background ratio starting after 6 hours and lasting until 24 hours [27]. In case of HCC the timing is different, as ICG is metabolized by normal hepatocytes and unexcreted because of bile ducts alteration, elightening the nodules even many days after the injection.…”
Section: Discussionmentioning
confidence: 99%